Rapid response and inter-organizational competition : Four international organizations, two key states, and the crisis in the Central African Republic - Welz, Martin (My University, 2019)
This chapter explores conflict management during the crisis in the Central African Republic (CAR) that erupted in late 2012 and was described as being on the verge of genocide. It focuses on the responses to that conflict by France and various international organizations such as the African Union, the Economic Community of Central African States, the European Union, and the United Nations. The chapter describes the CAR case suggests that competition between international organizations can delay an adequate response to a conflict and can lead to massive security problems on the ground. It provides a key role in deciding whether there is a rapid response or not. The chapter outlines the organizations’ mandates to demonstrate that overlapping mandates are one source of inter-organizational competition, which in the case of ECCAS-AU relations led to massive problems on the ground. It introduces the aforementioned key actors and analyzes their policies and actions.
Keywords: 320